FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PENGGUNAAN DIGITAL BANKING : LIVIN’ BY MANDIRI - Thomas Wahyudi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Seeing technological advances in the world, it is undeniable that technological developments has affected all industries in the world, including the banking industry. Technology in industry Banking is currently one of the most frequently used industries with the existence of digital banking that makes all public banking matters easier and more accessible done anywhere and anytime. Therefore, this research was conducted with the aim of finding know what are the factors that can affect the intention to use a digital banking by community, especially for digital banking Livin by Mandiri as a case study. Deep hypothesis This research has a positive impact, even with the risk of using digital banking can give positive results to the service. For this research, carried out with purposive sampling from Livin by Mandiri users as respondents. This research has collected 2,023 respondents and used a Likert scale of 1-5. From the results of this study, it can be seen that self-efficacy is the variable with the result that gives the highest influence, which explains how people's ability to use technology goes wrong one of the highest determining factors in the use of digital banking Livin by Mandiri.Keywords: Intention to Use, Technology Self Efficacy, Digital Banking